PENGEMBANGAN USAHA MICRO KECIL DAN MENENGAH (UMKM) SEBAGAI KEKUATAN STRATEGIS DALAM MEMPERCEPAT PEMBANGUNAN DAERAH - Abdullah Abidin (AkMen JURNAL ILMIAH, 2008)
as strategic strength in quickening area development. In this relation specially micro effort sector it is true occupy the strategic position in development as safety belt, because growth UMKM every year progressively mount the. Micro Effort Minimize and Middle own the important position, not only in absorbtion of labour and society prosperity in area, in a lot of their matter become the glue and stabilize the social difference problem. Refering to [the] mentioned, hence need the effort to grow the climate kondusif for growth UMKM in quickening area development Placing micro effort minimize and middle as especial target of development have to be based on by the good komitmen coordination and among government, pembisnis and institute the non business and also local society by applying Aggresive strategy being based on at network economics (Partner); micro Effort Development minimize and middle of entirety by supporting real and positive to human resource development (training Enterpreneur), technological, information, access the financing and also marketing, Market extension export, representing efficacy indicator develop;build the effort climate being based on nationality.